2018
DOI: 10.26599/tst.2018.9010038
|View full text |Cite
|
Sign up to set email alerts
|

Efficient helicopter−satellite communication scheme based on check-hybrid LDPC coding

Abstract: When implementing helicopter−satellite communications, periodical interruption of the received signal is a challenging problem because the communication antenna is intermittently blocked by the rotating blades of the helicopter. The helicopter−satellite channel model and the Forward Error Control (FEC) coding countermeasure are presented in this paper. On the basis of this model, Check-Hybrid (CH) Low-Density Parity-Check (LDPC)codes are designed to mitigate the periodical blockage over the helicopter−satellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…As an alternative to density evolution, EXIT charts approach is a useful tool to analyze the decoding thresholds of LDPC code ensembles and GLDPC code ensembles [35]- [37]. However, it has been found that conventional EXIT charts based iterative decoding threshold analysis on spatially coupled codes is disabled owing to the appearance of macro-convergence and micro-convergence in the decoding trajectory [38].…”
Section: Decoding Thresholds Of Sc-gldpc Codesmentioning
confidence: 99%
“…As an alternative to density evolution, EXIT charts approach is a useful tool to analyze the decoding thresholds of LDPC code ensembles and GLDPC code ensembles [35]- [37]. However, it has been found that conventional EXIT charts based iterative decoding threshold analysis on spatially coupled codes is disabled owing to the appearance of macro-convergence and micro-convergence in the decoding trajectory [38].…”
Section: Decoding Thresholds Of Sc-gldpc Codesmentioning
confidence: 99%
“…These schemes are really effective when the code length is sufficient, but may be difficult to implement in practical systems. When we consider the design of practical coding schemes, another valuable metric is the BER [15,16]. In fact, it is difficult for the eavesdropper to recover any information from the decoded message when she experiences a BER of about 0.5 and the errors are randomly distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high-speed data rate, orthogonal frequency division multiplexing (OFDM) [1,2] has been widely applied to the 4G mobile communication system, Wi-Fi, and some military communication systems [3][4][5][6][7]. However, its signals may have high peak-to-average power ratio (PAPR).…”
Section: Introductionmentioning
confidence: 99%